Performance Analysis of TiAlN/TiN PVD Coated Carbide Tools in High-Speed and Dry Machining of AISI 1070 Alloy Steel - Sumawijaya, Sumawijaya; Albert Hendi Yanto Larosa; Yakmuri Lubis; Burhan Hafid (JOURNAL OF MECHANICAL ENGINEERING MANUFACTURES MATERIALS AND ENERGY, 2024)
This study investigates the performance of TiAlN/TiN PVD-coated carbide tools in high-speed, dry machining of AISI 1070 alloy steel. AISI 1070 is a high-carbon steel known for its exceptional hardness, making tool wear a significant challenge. The research focuses on evaluating tool wear, wear mechanisms, and optimal cutting parameters. Quantitative assessments of flank wear (VB) were conducted, alongside detailed Scanning Electron Microscopy (SEM) analyses to identify the primary wear mechanisms, such as abrasion and adhesion. The study determined that the optimal cutting conditions for minimal tool wear include a cutting speed of 231 m/min, a feed rate of 0.1 mm/rev, and a depth of cut of 1 mm. The TiAlN/TiN coatings significantly enhanced the tools' wear resistance and longevity, maintaining their cutting-edge sharpness under strenuous conditions. Additionally, the coatings effectively minimized the formation of white layers on the machined surface, preserving the mechanical properties and surface integrity of the alloy. These findings demonstrate the coatings' superiority in reducing friction and heat generation during high-speed machining. The study provides valuable insights for industrial applications, highlighting the potential of TiAlN/TiN-coated carbide tools to improve tool performance, operational efficiency, and overall productivity in high-speed machining environments.